Forecasts of inflation and interest rates in no-arbitrage affine models - Nikolay Gospodinov; Bin Wei (Federal Reserve Bank of Atlanta, 2016)
In this paper, we examine the forecasting ability of an affine term structure framework that jointly models the markets for Treasuries, inflation-protected securities, inflation derivatives, and oil future prices based on no-arbitrage restrictions across these markets. On the methodological side, we propose a novel way of incorporating information from these markets into an affine model. On the empirical side, two main findings emerge from our analysis. First, incorporating information from inflation options can often produce more accurate inflation forecasts than those based on the Survey of Professional Forecasters. Second, incorporating oil futures tends to improve short-term inflation and longer-term nominal yield forecasts.
Keywords: G12; E43; E44; C32; 330; bond prices; TIPS; inflation derivatives; oil prices; no-arbitrage; affine models; out-of-sample forecasting